Civic media : technology, design, practice - Gordon, Eric, 1973-; Mihailidis, Paul, 1978- (The MIT Press, 2016)
Examinations of civic engagement in digital culture--the technologies, designs, and practices that support connection through common purpose in civic, political, and social life. Countless people around the world harness the affordances of digital media to enable democratic participation, coordinate disaster relief, campaign for policy change, and strengthen local advocacy groups. The world watched as activists used social media to organize protests during the Arab Spring, Occupy Wall Street, and Hong Kong's Umbrella Revolution. Many governmental and community organizations changed their mission and function as they adopted new digital tools and practices. This book examines the use of "civic media"--The technologies, designs, and practices that support connection through common purpose in civic, political, and social life. Scholars from a range of disciplines and practitioners from a variety of organizations offer analyses and case studies that explore the theory and practice of civic media. The contributors set out the conceptual context for the intersection of civic and media; examine the pressure to innovate and the sustainability of innovation; explore play as a template for resistance; look at civic education; discuss media-enabled activism in communities; and consider methods and funding for civic media research. The case studies that round out each section range from a "debt resistance" movement to government service delivery ratings to the "It Gets Better" campaign aimed at combating suicide among lesbian, gay, bisexual, transgender, and queer youth. The book offers a valuable interdisciplinary dialogue on the challenges and opportunities of the increasingly influential space of civic media